Determnan Keputusan Penggunaan Dompet Digital Dengan Minat Guna sebagai Variabel Intervening: - Nur Sabiatul Aulia; Sugianto Sugianto; Nurul Jannah (El-Mujtama: Jurnal Pengabdian Masyarakat, 2023)
In the era of increasingly advanced developments, it requires humans to follow developments that occur in order to support life. The development of technology and speed in obtaining information is certainly very influential in activities to improve financial performance, one of which is the development of technology-based businesses. This study aims to determine the effect of the level of risk, benefit, and ease to use on the decision to use use a digital wallet with interest in use as an intervening variable. This research was conducted using a quantitative approach and used three independent variables, namely the level of risk (X1), benefit (X2), and ease to use (X3), then there is one dependent variable, namely the decision to use (Y), and one intervening variable, namely interest in using (Z). The samples used were students of the State Islamic University of Nort Sumatera in 2018 as many as 99 samples. The type of data use in this study is primary data by distributing questionnaires to the respondents. While the data analysis techniques used is path analysis. The results of this study indicate that (i) the level of risk has a positive and significant effect on interest in use, (ii) usefulness has a positive and significant effect on interest in use, (iii) ease to use has a positive and significant effect on interest in use, (iv) interest in use has a positive effect and significant to the decision to use, (v) the level of risk has no significant effect on the decision to use through interest in use, (vi) benefit has no significant effect on decisions to use through interest in use, (vii) ease of use has a positive and significant effect on decisions to use through interest in use. Interest path analysis was tested to be able to mediate the relationship between the level of risk, benefit, and ease of use on the decision to use a digital wallet. Keywords : Level of risk, Benefit, Ease to use, Decision to use, Digital wallet